2020
DOI: 10.1038/s41598-020-59944-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of HIV-1 Molecular Epidemiology in Nigeria: Origin, Diversity, Demography and Geographic Spread

Abstract: Nigeria has the highest number of AIDS-related deaths in the world. In this study, we characterised the HIV-1 molecular epidemiology by analysing 1442 HIV-1 pol sequences collected 1999-2014 from four geopolitical zones in Nigeria using state-of-the-art maximum-likelihood and Bayesian phylogenetic analyses. The main circulating forms were the circulating recombinant form (CRF) 02_AG (44% of the analysed sequences), CRF43_02G (16%), and subtype G (8%). Twenty-three percent of the sequences represented unique re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Diverse HIV‐1 subtypes and recombinant forms (CRF02_AG, G, A, B, C, D, CRF06_cpx, URFs, etc.) have been previously characterized in the country 7 . Several HIV‐1 high‐risk groups such as commercial sex workers, 8,9 voluntary blood donors, 10,11 long‐distance drivers, 12–14 mammy markets contiguous to military facilities, 15 etc., have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse HIV‐1 subtypes and recombinant forms (CRF02_AG, G, A, B, C, D, CRF06_cpx, URFs, etc.) have been previously characterized in the country 7 . Several HIV‐1 high‐risk groups such as commercial sex workers, 8,9 voluntary blood donors, 10,11 long‐distance drivers, 12–14 mammy markets contiguous to military facilities, 15 etc., have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Subtypes A and G have also been previously reported as circulating in Oyo state as well as in other parts of Nigeria. A recent study identified CRF02_AG, as well as subtypes G and A as the predominant circulating HIV-1 strains in Ibadan, Nigeria 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings in this study observed more subtypes in Ibadan metropolis (urban settlement) compared to Saki town (rural settlement). Recent studies using phylodynamic tools have suggested that HIV-1 strains originate and expand in urban areas before migrating to smaller rural centers 6 . There is the need to describe the phylodynamics of HIV-1 subtypes in other states of the country as this will shed further light into the diversity of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reconstructed the viral diffusion patterns between locations in SPREAD [56] and examined the viral migration profiles within and outside the GPC. A Bayes Factor (BF) test was applied to determine significant non-zero transition rates and a cut-off of BF = 3 was used [41,56,57].…”
Section: Bayesian Phylogeographic Analysismentioning
confidence: 99%